Parental Influence on Financial Literacy and Behavior of Generation Z Students at UPN Yogyakarta - Mu’afi, Muhammad Irfan; Koorag, Satrio Tegar Gunung; Sagita, Virginia Ayu (Research Parks Publishers, 2024)
This study aims to determine the role of parents in providing financial education to Generation Z students at UPN Yogyakarta and how this education impacts their financial behavior. Utilizing a phenomenological research approach, the study involved in-depth interviews with ten respondents from UPN Yogyakarta. The research explores the factors that lead these students to recognize the importance of financial education imparted by their parents, along with other psychological and economic factors that underscore the necessity of financial literacy for wise money management. The findings reveal several key insights. Firstly, parents significantly shape their children's financial behaviors, with those who receive early financial education from their parents demonstrating better money management skills. Secondly, students who did not receive financial education from their parents often turn to digital platforms like YouTube and Instagram to gain financial knowledge. Thirdly, students from economically disadvantaged backgrounds are more likely to seek financial literacy independently to avoid financial pitfalls. Additionally, psychological factors, such as self-awareness and resilience, play a crucial role in shaping financial behavior. Lastly, there is a notable variation in financial literacy among the respondents, influenced by their family backgrounds and the financial education they received. These results underscore the importance of parental involvement in financial education and the need for targeted strategies to enhance financial literacy among students, particularly those from less privileged backgrounds. The study highlights the potential benefits of incorporating financial education into early childhood development to foster prudent financial behaviors.